Comprehensive assessment of the premature fetus condition in pregnant women with prelabor rupture of membranes - S. P. Posokhova; O. U. Kucherenko (Kazimierz Wielki University, 2020)
Introduction. Perinatal hypoxia - ischemia is the cause of 30 - 35% of neonatal fatalities. Inflammatory factors such as prolonged rupture of membranes, maternal fever, are often accompanied by chorioamnionitis, associated with the birth of low Apgar scores children, convulsions of newborns and the diagnosis of "birth asphyxia" in infants who then develop cerebral palsy. The objective: to assess the condition and behavior of the premature fetus in pregnant women with prelabor rupture of membranes Materials and methods. The treatment (main) group (TG) consisted of 80 pregnant women with singleton pregnancies who gave birth to premature infants at gestation 27 + 6 - 34 weeks. The comparison group (CG) included 60 pregnant women at 27 + 6 - 34 weeks of gestation who were hospitalized with spontaneous preterm birth. Ultrasound examination to determine the behavior of the fetus on the scale of the neurological test KANET was performed. Results and discussion. The most common complication was the threat of abortion in the third trimester in CG pregnant women (76.6%), which is 1.3 times more if compared with TG (60%) data. Placental dysfunction and fetal growth retardation were 2 times greater in CG (TG-16.2%, CG-35%). One in five pregnant women in both groups had dehydration, which complicated the fetus's development and condition. The long anhydrous period of more than 48 hours was in 22 (36.6%) CG pregnant women, which is 10 times more often than in the treatment group. In 7 (11.6%) cases, CG women had chorioamnionitis. KANET neurological test showed that the fetuses of the TG pregnant women with prelabor rupture of memebranes, who underwent neuroprotection with magnesium sulfate in 87.5% of cases showed normal behavior. The fetuses of pregnant women from the CG had normal neurological behavior in only 64.5% of cases , i.e.1.3 times less than in the TG. Conclusions: Prelabor rupture of membranes in premature pregnancy affects the course of pregnancy, leads to premature birth, increases the risk of intrauterine infection, changes the antenatal behavior of the fetus and can lead to hypoxic - ischemic brain damage with subsequent adverse effects.